Describing and Interacting with Functional, Symbolic and Semantic Systems - Aitken, Ashley (Conference Publishing Proceedings, 2012)
A conceptual explanation of descriptions of systems at the physical, functional, symbolic and semantic level is given. A notation for clearly distinguishing physical from functional, symbolic, and semantic states is defined (together with its inverse). The Computational Theory of Mind and its relationship to the description of systems are explained. The interaction of human computational systems with functional, symbolic, and semantic systems is considered. One conclusion is that semantic systems are easier to interact with as long as they can be trusted to really be semantic systems and in the semantic states the human deduces they seem to be in. A general approach to engineering systems is to use subsystems with different levels of description but be clear about what these are for each subsystem.